Clinical Outcomes for Sexual and Gender Minority Adolescents in a Dialectical Behaviour Therapy Programme - Camp, J. (Behav Cogn Psychother, 2024)
BACKGROUND: Sexuality and gender minoritised (SGM) adolescents are at increased risk of self-injury and suicide, and experience barriers to accessing mental health support. Dialectical Behaviour Therapy (DBT) is an effective treatment for self-injury and emotion dysregulation in adolescent populations, but few studies have published outcomes of DBT for SGM young people. AIMS: This study aimed to investigate treatment outcomes and completion for SGM adolescents and their cisgender and heterosexual peers, in the National & Specialist CAMHS, DBT service (UK). METHODS: Treatment completion, opting out before and during treatment were examined for sexual and gender identity groups, as well as changes by the end of treatment in emotion dysregulation, self-injury, inpatient bed days, emergency department attendances, and borderline personality disorder, depression, and anxiety symptoms. RESULTS: SGM adolescents were over-represented in this service, even after considering their increased risk for self-injury. No statistically significant differences were found for treatment completion between the sexual orientation and gender identity groups although there were patterns indicating possible lower treatment uptake and completion that warrant further investigation. Clinical outcomes for treatment-completers showed improvement by the end of DBT for each group, with few exceptions. DISCUSSION: These results are from relatively small subsamples, and it was not possible to separate by sex assigned at birth. Findings should be treated tentatively and as early indications of effect sizes to inform future studies. This study suggests that DBT could be a useful treatment for SGM adolescents in a highly specialist treatment setting.